Influencia de la refusion en las propiedades mecanicas y composicion quimica de aleaciones odontologicas - Yamakami, W. J. [UNESP]; Ferreira, I. [UNESP] (My University, 1999)
The objective of the study presented in this article was to analyze the influence of remelting of two odontological alloys: Dentorium and Steeldent, on the mechanical properties and on the chemical composition. For the two alloys, samples, containing 10% and 50% new alloy, were subjected to tensile test, micrography and chemical analysis. The alloys presented similar mechanical properties, except for the elongation, which presented higher values for the Dentorium 50% new alloy. This is due to the smaller carbides formed in this sample. The remelting itself seems not to be responsible for these differences, but they are probably due to the lack of a good control of the casting process. The micrography showed a dendritic column matrix, with carbides in the interdentric region and inside dendritic grain. In the chemical composition was observed few elements percentage change.
Influence of remelting on mechanical properties and chemical composition of odontological alloys
Keywords: Carbides; Cobalt alloys; Composition effects; Mechanical properties; Metal casting; Metallographic microstructure; Remelting; Tensile testing; Micrography; Odontological alloys; Dental alloys